EFFECT OF PRE-HARVEST AMINOETHOXYVINYLGLYCINE (AVG) APPLICATION ON BIOACTIVE COMPOUNDS AND FRUIT QUALITY OF PLUM (PRUNUS SALICINA LINDELL CV. BLACK BEAUTY) AT THE TIME OF HARVEST AND DURING COLD STORAGE - E. Kucuker; B.Ozturk; H. Aksit; N. Genc (Journal of Animal and Plant Sciences, 2015)
This study aimed at determining the effects of preharvest aminoethoxyvinylglycine (AVG) applications in different doses on the fruit quality of Black Beauty plum during cold storage. Plum trees were applied AVG doses (100 and 200 mgL-1) two weeks before the estimated harvest date. Change in physical, mechanical, chemical and bioactive compounds in fruit samples were determined at weekly intervals. Applications of AVG delayed the parameters related with maturation such as weight loss, color and firmness during storage. At the end of 28 days, the least weight loss was with 200 mgL-1 AVG application, while the highest weight loss (%) was in control treatment. While, the lowest fruit firmness (11.31 N) was recorded in control fruits, the highest (26.78 N) was obtained with 200 mgL-1 AVG application. At the end of the storage duration, all applications were statistically similar in terms of TSSC value. The applications of AVG had a significant effect on the bioactive compounds of the fruits. Overall, both total phenolics and total antioxidant acitivity exhibited a linear decrease with increasing the storage duration regardless of AVG treatments. A similar decrease with storage was also observed in chlorogenic acid, epicatechin, catechin, caffeic acid, p-coumaric acid, quercetin. Naringenin displayed a significant decrease due to AVG applications during the cold storage.
Keywords: Antioxidant; cold storage; chlorogenic acid; firmness; phenolic; plum